Proteolytic processing of the protein tyrosine phosphatase α extracellular domain is mediated by ADAM17/TACE - Kapp, Katja; Siemens, Jan; Häring, Hans-Ulrich; Lammers, Reiner (European journal of cell biology, 2012)
The receptor protein tyrosine phosphatase alpha (PTPα) is involved in the regulation of tyrosine kinases like the Src kinase and the insulin receptor. As with other PTPs, its function is determined by alternative splicing, dimerisation, phosphorylation and proteolytical processing. PTPα is cleaved by calpain in its intracellular domain, which decreases its potential to dephosphorylate Src kinase. Here, we demonstrate that PTPα is also processed in the extracellular domain. Extracellular processing was exclusively found for a splice variant containing an extra nine amino acid insert three residues amino-terminal from the transmembrane domain. Processing was sensitive to the metalloprotease-inhibitor Batimastat, and CHO-M2 cells lacking a disintegrin and metalloproteinase 17 (ADAM17; tumor-necrosis-factor α converting enzyme) activity were not able to cleave PTPα. After transient overexpression of ADAM17 and PTPα in these cells, processing was restored, proving that ADAM17 is involved in this process. Further characterization of the consequences of processing revealed that dephosphorylation of the insulin receptor or activation of Src was not affected but focus formation was reduced. We conclude that extracellular proteolytic processing is a novel mechanism for PTPα regulation.
Gesehen am 06.12.2021